The Aortic Root Replacement Procedure: 12-year Experience From the Australian and New Zealand Society of Cardiac and Thoracic Surgeons Database - Dhurandhar, V.; Parikh, R.; Saxena, A.; Vallely, M.; Wilson, M.; Black, D.; Tran, L.; Reid, Christopher; Bannon, P. (Elsevier, 2014)
Background: The aortic root replacement procedure (ARR), is often considered the gold standard in the management of aortic root and ascending aorta aneurysms. Our aim was to review the Australian experience with this procedure to ascertain early and late outcomes of mortality and morbidity. Methods: We reviewed the Australian and New Zealand Society of Cardiac and Thoracic Surgeons' (ANZSCTS) database for patients undergoing ARR. Preoperative, intraoperative and postoperative variables were analysed. Multiple regression was performed to determine independent predictors of 30-day mortality and permanent stroke, and predictors of late death. Survival estimates were obtained by cross-linking the ANZSCTS database with the Australian Institute of Health and Welfare's National Death Index database. Results: Between January 2001 and December 2011, 954 patients underwent ARR with a mean age of 56. ±. 15.2 years. The overall 30-day mortality was 5.9% (n = 56) with a permanent stroke rate of 2.3% (n = 21). The elective surgery mortality was 3.6%. Long-term survival was estimated as 84.4% and 68.7% at 5 and 10 years, respectively. Conclusions: Aortic root replacement surgery reveals acceptable early mortality, low postoperative stroke rates, and acceptable long-term survival.